The Wnt pathway can stabilize hybrid phenotypes in the epithelial-mesenchymal transition: A logical modeling approach. (August 2022) - Silveira, Daner Acunha; Gupta, Shantanu; Sinigaglia, Marialva; Mombach, José Carlos Merino
Abstract: The Wnt pathway is important to regulate a variety of biochemical functions and can contribute to cancer development through its influence on the epithelial-mesenchymal transition (EMT). Multiple circuits have been reported to participate in the regulation of the Wnt signaling, however, the way these circuits coordinately regulate this signaling is still unclear. Moreover, the mechanisms responsible for the appearance of hybrid phenotypes (cells presenting both E and M features) are not well determined. The hybrid phenotype can present much higher metastatic potential than the mesenchymal phenotype. In this study, we propose a Boolean model of the Wnt pathway signaling contemplating recent published biochemical information on hepatocarcinoma. The model presents good coherence with experimental data for perturbed and wild-type cases. With the model, we propose two new molecular circuits involving several molecules that can stabilize hybrid states during the EMT. Moreover, we found that the two well studied circuits, AKT1/ β -catenin and SNAIL1/miR-34, can cooperate with the predicted ones to favor the stabilization of the hybrid states. These findings highlight some possible unrecognized mechanisms during Wnt signaling and may provide alternative therapeutic strategies to control cancer metastatization. Graphical Abstract: ga1 Highlights: The model describes the epithelial-mesenchymal transition induced by the Wnt signaling in hepatocarcinoma cells. The simulations indicate the existence of multiple hybrid phenotypes. The model predicts four new positive circuits which may stabilize the hybrid phenotypes. The results suggest that the predicted circuits can favor the stabilization of hybrid states. The present study suggests alternative therapeutic strategies to control cancer metastatization